Compatibilizing of polycarbonate and poly(methly methacrylate) blends with montmorillonite nanomer 1.42E (MMT) - Norfaizah Zainal Abidin, 1989-, author; Munirah Mokhtar, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Kimia - Polimer)) - Universiti Teknologi Malaysia, 2013